Pengaruh Faktor Internal Dan Eksternal TerhadapAudit Delay Pada Perusahaan Manufaktur YangTerdaftar Di Bei Periode 2013-2015 - Setyadewi, Merlia; , Rina Trisnawati, Dra,Ak,Msi,Ph.D (2017)
The purpose of this research is to know the influence of internal and external factors to the audit delay at manufacturing companies has registered in BEI 2013-2015. Internal factors consist of profitability, firm size and the corporate income, while the external factors consist of auditor's opinion and the auditor's reputation. In this study the type of data used is quantitative data with a population of 149 companies listed in Indonesia Stock Exchange in 2013-2015. The analytical method used is logistic regression analysis with sample totaling 89 companies were selected based on purposive sampling method for 3 periods. Based on the analysis it can be concluded that the profitabilities not significant effect on the audit delay, the company size no significant effect audit delay, the profit or less of company has no significant effect on the audit delay, the audit opinion has no effect significantly to the audit delay, and the audit reputation have a significant effect on the audit delay.